Resilience and robustness of IPM in protected horticulture in the face of potential invasive pests. (July 2017) - Pérez-Hedo, M.; Suay, R.; Alonso, M.; Ruocco, M.; Giorgini, M.; Poncet, C.; Urbaneja, A.
Abstract: Recently, various approaches for the biological control of major pests in protected crops have successfully been adopted. These successes have primarily occurred via the selection, release and/or conservation of generalist native predators that naturally colonize Mediterranean crops that are highly adapted to local environmental conditions. These generalist predators have resulted very effective in controlling key pests; as a result, pesticide use has been reduced considerably. In addition, because these predators are typically highly polyphagous, horticultural crops have become more resilient to newly emerging pests, which are preyed upon by these predators. Possibilities to further strengthen pest management in horticultural crops have recently arisen, such as the use of beneficial microbes (BM) to induce plant resilience. In this review, we used a tomato crop as an example to present two new, highly interrelated plant defense induction strategies: the use of Miridae zoophytophagous predators and the use of Trichoderma spp. microbial biological control agents. Both the mirid predators and Trichoderma symbiotic fungi can activate direct and indirect plant defense responses, which may increase the robustness of pest management against invading organisms. The practical use of these new approaches is discussed. Highlights: Possibilities to further strengthen pest management in horticultural crops exist. Mirid predators and Trichoderma symbiotic fungi can activate plant defences. Both may increase the robustness of pest management against invading pests.